EKSPRESI PUITIK DALAM ANTOLOGI PUISI DWIBAHASA M.AAN MANSYUR: KAJIAN TERJEMAHAN PUISI - I Gusti Agung Sri Rwa Jayantini; Ronald Umbas; Ni Komang Arie Suwastini; Putu Desi Anggerina Hikmaharyanti (Kajian Linguistik dan Sastra, 2022)
Poetic expression in poetry of different languages is an interesting study because this literary work reflects not only the personal expression of the poet but also the world through diction and figurative language that carry certain moral messages. This study aims to reveal the translation of comparative and contradictory figurative languages which are used to convey poetic expressions found in the poems about love and the existence of a poem, which are understood by the poet, M.Aan Mansyur, in his bilingual poetry collection, "There is No New York Today." The method used in this research was a combination of content analysis and stylistic approach. The writer compared figurative language in two languages, Indonesian and English and the strategies applied to translate them. This study found that first, poetic expressions were expressed in three ways, namely (1) comparative figurative language represented by metaphors, (2) contradictory figurative language manifested through paradoxes, and (3) combinations of comparison and contradiction in one verse of poetry, and second, the translation strategies applied were literal translation and literal-meaning translation. These two findings are useful for exploring the use of comparative and contradictory figurative language as well as how to translate them so that the message is conveyed perfectly and the language style used by the translator is as beautiful as the poetry of the source language.